RANCANG BANGUN TUNGKU PADA ALAT INSINERATOR - Alma Fadlillah; Sigit Mujiarto; Suyitno (POLITALA PRESS, 2026)
The accumulation of waste has become a serious issue in Indonesia due to limited landfill space and the lack of an effective waste management system. One alternative solution is the use of an incinerator as an environmentally friendly waste-burning device. This study aims to design and construct the combustion chamber of an incinerator and to test its effectiveness on three types of organic waste variations: dry, wet, and mixed. The method used is a design and build approach, which includes designing with AutoCAD and SketchUp, constructing the physical structure, and conducting combustion tests. The results show that the chamber can accommodate 2–3 kg of waste per batch and can reach a maximum temperature of up to 110°C. The fastest burning time was achieved with dry waste at 16 minutes and 21 seconds, with a combustion rate of 1.95 grams/second. This incinerator, with its simple design and low cost, is effective in reducing waste volume and produces ash that can be used as fertilizer. It is hoped that this incinerator can be widely adopted by communities to help address the waste problem.